Dr. Socorro Ortiz — Deep Plane Facelift — Brussels - Ortiz, Socorro (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Socorro Ortiz, practicing in Brussels, Belgium. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003331; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; belgium; brussels